Design of new structure of multilevel inverter based on modified absolute sinusoidal PWM technique - Asef A. Saleh; Rakan Khalil Antar; Harith Ahmed Al-Badrani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The advantage of multilevel inverters is to produce high output voltage values with distortion as minimum as possible. To reduce total harmonic distortion (THD) and get an output voltage with different step levels using less power electronics switching devices, 15-level inverter is designed in this paper. Single-phase 11-switches with zero-level (ZL) and none-zero-level (NZL) inverter based on modified absolute sinusoidal pulse width modulation (MASPWM) technique is designed, modelled and built by MATLAB/Simulink. Simulation results explained that, multilevel inverter with NZL gives distortion percent less than that with ZL voltage. The THD of the inverter output voltage and current of ZL are 4% and 1%, while with NZL is 3.6% and 0.84%, respectively. These results explain the effectiveness of the suggested power circuit and MASPWM controller to get the required voltage with low THD.